Barriers for HIV testing during pregnancy in Southern Brazil - Rosa,Humberto (2006)
OBJECTIVE: To assess HIV testing rate and determine risk factors for not have been tested during pregnancy. METHODS: A cross-sectional study was carried out in Porto Alegre, Southern Brazil, from December 2000 to February 2001. Socioeconomic, maternal and healthcare variables were obtained by means of a standardized questionnaire. Crude and adjusted odds ratios and their 95% confidence intervals were obtained in logistic regression models. RESULTS: A total of 1,642 mothers were interviewed. Of them, 94.3% reported being offered HIV testing before or during pregnancy or during labor; 89 mothers (5.4%) were not tested or did not know if they were tested. Attending fewer than six prenatal visits, being single and younger than 18 years old were relevant barriers preventing HIV testing. There was found a relationship between maternal schooling and the category of prenatal care provider. Having low 22.20 (12.43-39.67) or high 3.38 (1.86-7.68). schooling and being cared in the private sector strongly reduced the likelihood of being HIV tested. CONCLUSIONS: The Brazilian Health Ministry's recommendation for universal counseling and HIV testing has been successfully implemented in the public sector. In order to improve HIV testing coverage, new strategies need to target women cared in the private sector especially those of low schooling.